Importing Clay for Local Pottery Production in the 4th Century b.c. at Tell el-Timai, Egypt. (2nd January 2018) - Hudson, Nicholas; Gentelli, Liesel; Trampier, Joshua
ABSTRACT: Archaeological evidence of ceramic production most commonly consists of locally procured raw materials. Excavations at Tell el-Timai in Lower Egypt recovered raw fine marl clay from two transport jars in the vicinity of pottery kilns dating to the 4th centuryb.c. Production wasters of small perfume bottles produced in the same fine marl clay were found inside the kilns. The marl clay inside the jars pointed to an origin outside of Lower Egypt. Samples of the clay and wasters, along with a confirmed locally sourced sample, were subjected to X-Ray Fluourescence (XRF) analysis, revealing significant differences in their chemical compositions. The results of the analysis are compared to published Egyptian data and an Upper Egyptian provenience is suggested because the raw clay is consistent with available comparative XRF data.